Efficacy and safety of eltrombopag in Chinese patients with chronic immune thrombocytopenia: stage 2 results from a multicenter phase III study. (2nd January 2022) - Liu, Xiaofan; Hou, Ming; Li, Junmin; Jin, Jie; Huang, Meijuan; Yu, Ziqiang; Xu, Xiaojun; Zhang, Xiaohui; Yang, Renchi
Abstract: This phase III, randomized, placebo-controlled study conducted in three stages (6-week, randomized, placebo-controlled stage 1; 24-week, open-label stage 2; and continuous extension stage 3) assessed the long-term efficacy and safety of eltrombopag use in Chinese patients with chronic immune thrombocytopenia (ITP). This article presents the results from stage 2. Overall, 150 patients (placebo-eltrombopag [P-E], 50; eltrombopag-eltrombopag [E-E], 100) received open-label eltrombopag. The median platelet count was maintained between 41 × 10 9 /L and 80 × 10 9 /L. Most patients in both groups (P-E, 90.0%; E-E, 81.8%) achieved platelet counts ≥30 × 10 9 /L and ≥2 times the baseline platelet count at least once with eltrombopag treatment. Overall, 32% of patients achieved platelet counts ≥50 × 10 9 /L in ≥75% of platelet count assessments. Both groups showed a decreased tendency to infrequent bleeding and clinically significant bleeding events during stage 2 compared with baseline. Among patients who received ≥1 ITP medication at baseline, 70.4% in the P-E group and 40.8% in the E-E group reduced or permanently stopped ≥1 of their ITP medications. The stage 2 results further demonstrated a sustainable long-term efficacy and good tolerability of eltrombopag with a favorable benefit–risk ratio in Chinese chronic ITP patients. Trial registration: Clinicaltrials.gov NCT01762761. Registered 8 January 2013, https://clinicaltrials.gov/ct2/show/NCT01762761